BACTERIAL QUALITY AND DEPURATION OF THE GREEN MUSSEL PERNA VIRIDIS FROM NATURAL BEDS - MALARVANNAN, G.; EDWARD, J. K. PATTERSON (Journal of Indian Fisheries Association, 2015)
Green mussel (Perna viridis) and sea water from their natural beds onthe coastal areas of Porto Novo were studied between April and August 1996for their bacterial quality. Water samples from the beds were also analysedfor their physico-chemical parameters. The total bacterial count of nn.1sselsfrom natural beds as well as bed waters ranged 103 organisms per grammeof n1ussel meat suspension and per Inillilitre of sea water. The faecal coliformswere found to be within the permissible limits. Pathogenic bacteria such asSabnonella spp., Streptococcus spp. and Staphylococcus spp. were absent.The variations in pH, temperature, salinity and dissolved oxygen of theseawater samples were insignificant. The mussels were subjected to depurationby different methods among which chlorination was found to be mosteffective.Keywords : Mussel, Perna viridis, bacterial quality, depuration